Rewriting leadership with narrative intelligence : how leaders can thrive in complex, confusing and contradictory times - Morgan, Greg (Emerald Publishing Limited, 2019)
Leadership is a slippery concept. Researchers disagree on its essence, describing it variously as behaviours, character traits or styles. Effective leaders understand that we make meaning of our experiences by creating stories we believe to be true, but which are largely based on fragmentary evidence filtered through our biases, beliefs and dispositions. Rewriting Leadership with Narrative Intelligence draws on a range of disciplines and scholarly traditions to build a compelling case for a new perspective on leadership, seeing it as a deeply embodied, intuitive skill of curating shared narratives, in influence relationships. Defining narrative intelligence as 'our ability to evaluate the efficacy of the stories we create to serve our needs, our capacity to rewrite them, and the practical skill to take effective action', this book methodically outlines how leaders cultivate their own narrative intelligence to: Become the person they seek to be by aligning narratives and core values with actions. Navigate through the challenging leadership space of populism and the erosion of traditional values. Ethically curate the narrative others hold of them. Strengthen self-efficacy, take more effective actions, and avoid stories which inadvertently undermine goals. Communicate with trust and influence. Build energy and alignment within teams by generating shared narratives. Cultivate a culture of narrative intelligence. This book will prepare leaders to reshape their own and others' stories to be more aligned with achieving goals and wellbeing. It will prove a useful resource to undergraduates and post-graduates in courses on leadership and management, as well as organizational development consultants and senior executives.
Keywords: Leadership.; Artificial intelligence.; Business & Economics -- Leadership.; Management: leadership & motivation.; elektronické knihy; electronic books